Two dimensional debonding failure in adhesively bonded tiles. (September 2018) - Feldfogel, Shai; Rabinovitch, Oded
Highlights: The two-dimensional geometrically irregular evolution of debonding failure in thermally loaded tiling systems in studied. The unstable nature of the failure mechanism is revealed and quantified by studying the mechanism's non-monotonous equilibrium paths. The effects of different tile geometries on the nature and stability of the structural response are investigated. An extended high order multi layered analytical plate model, a corresponding finite element, plate-like cohesive interfaces, and a nonstandard pseudo arc length procedure are combined to form a general analytical computational platform. Abstract: Adhesively bonded tiling systems are extensively used in numerous applications. The most common, and critical, failure mechanism of such systems is interfacial debonding, which might precipitate the falling of tiles. Modeling the evolution and propagation of this failure mechanism presents considerable analytical and computational challenges. The present work aims to face the manifold challenges involved in analyzing the failure mechanism, using a specially tailored multi layered plate model and a corresponding triangular finite element. Following an introduction and the derivation of the methodologies, a numerical example considers the evolution of debonding failure in building-type tiling systems under thermal loading. Special attention is given to the geometrically irregular propagation of the debonding mechanism, to the stability (and instability) characteristics of the process, and to the effects of different tile geometries on the nature of the response. The results show that at a critical load, the system invariably snaps, and the debonding mechanism becomes unstable. This phenomenon is looked into by examining equilibrium paths, interfacial peeling traction distributions, and displacement fields, which shed light on the unstable nature of the problem from a qualitative, as well as a quantitative, point of view.